The analysis of librarian digital literacy of universities in Bali - Haryanti, Ni Putu Premierita; Suhartika, I Putu; Harsana, I Ketut Gede (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. This research focuses on the digital literacy of public university librarians in Bali. Digital literacy skills are really needed by librarians to improve the quality of services, especially in the development of information technology. Data Collection Methods. The method in this research is descriptive quantitative. The population and sample used in this research were all 61 State University Librarians in Bali. The sampling technique used was total sampling. Data collection was carried out through questionnaires, observations and interviews Data Analysis. This research uses multiple linear regression analysis using the Statistical Package of Social Science (SPSS) version 25 program. Results and Discussion. The research results show that the digital literacy of state university librarians in Bali is quite good. However, librarians need to improve their abilities in terms of creating the latest news and understanding contained in websites or library sites. Conclusion. Digital literacy has an influence on the competence of state university librarians in Bali. In this regard, librarians need to actively participate in training and seminars on digital literacy and be open to developing information technology. The implication of this research for the library sector is to help librarians evaluate the quality of digital literacy in higher education.